Pengaruh Modal Usaha, Upah Tenaga Kerja, Dan Lama Usaha Terhadap Pendapatan Umkm Di Kecamatan Majalaya Kabupaten Karawang - Umi Widyaningrum; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study is intended to determine the effect of business capital (X1), labor wages (X2) and length of business (X3) on MSME income (Y) in Majalaya District, Karawang Regency. This study used a quantitative descriptive verification method and data were obtained by distributing questionnaires which were distributed to 92 respondents from MSMEs in Majalaya District, Karawang Regency. Data analysis was carried out using path analysis and the help of the SPSS application version 24. The results showed that the venture capital variable obtained an average score of 4,36, which was categorized as good, the labor wage variable obtained an average score of 4,03, which was categorized as good, the old variable effort obtains an average score of 4,44, which is categorized as very good while the income variable obtains an average score of 4,23, which is categorized as good. The results of the descriptive test show that the variables of business capital and labor wages do not significantly influence MSME income, the magnitude of the influence of these two variables is 1.06% and 0.23%. While the length of business variable affects MSME income, the magnitude of the influence of the length of business variable on MSME income is 52.76%. However, when testing the hypothesis shows that there is a simultaneous effect of business capital, labor wages and length of business on MSME income. The magnitude of the influence of business capital, labor wages and length of business on MSME income is 54.05%. The influence of other variables outside the model is 45.95%. Keywords: Business capital, labor wages, length of business, income